2019
DOI: 10.1002/ajh.25693
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation for aplastic anemia with pre‐transplant conditioning using fludarabine, reduced‐dose cyclophosphamide, and low‐dose thymoglobulin: A KSGCT prospective study

Abstract: The optimal pre-transplant conditioning for aplastic anemia (AA) remains unclear. We performed a prospective study on allogeneic transplantation from a related or unrelated donor for adult patients with AA. We assessed whether reduced-dose cyclophosphamide (CY) could decrease toxicity while maintaining engraftment, and low-dose thymoglobulin could safely prevent graft-vs-host disease (GVHD). The pretransplant conditioning regimen consisted of fludarabine 120 mg/m 2 , CY 100 mg/kg, and thymoglobulin 2.5 mg/kg w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A relatively high incidence of MC has been reported in patients receiving HSCT for AA [11,14,16], and MC has been found to be associated with GF [12,20]. In the present study, the probability of SGF was associated with the time that had elapsed from HSCT, as well as the number of RHCs present in the recipient at MC onset.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A relatively high incidence of MC has been reported in patients receiving HSCT for AA [11,14,16], and MC has been found to be associated with GF [12,20]. In the present study, the probability of SGF was associated with the time that had elapsed from HSCT, as well as the number of RHCs present in the recipient at MC onset.…”
Section: Discussionsupporting
confidence: 53%
“…However, for patients in whom MC occurs early after transplantation and the RHCs reach level 3, the disease progresses quickly, and timely treatment is therefore of the essence. The impact of allo-HSCT and MC has been found to be associated with the conditioning regimen and donor source [11,20]. The present study suggested that donor/recipient sex-mismatching was a risk factor for MC, especially male donor to female patients in MSD-HSCT.…”
Section: Discussionmentioning
confidence: 56%
“…As a purine analog, Flu bears potential immune and lymphocyte clearance effects and has wide applicability and low toxicity. It has been applied to the SAA transplantation conditioning regimen and has achieved a substantial curative effect [24, 25]. Simultaneously, combined ATG therapy has achieved the effect of long-term removal of T lymphocytes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled aGVHD and cGVHD were 55 and 33%, respectively. Although most of these GVHD were well-managed and not lethal, they certainly caused a longer hospitalization period, increased medical burden, and reduced the quality of life (38,39).…”
Section: Discussionmentioning
confidence: 99%